Glucocorticoid Receptor Function Regulated by Coordinated Action of the Hsp90 and Hsp70 Chaperone Cycles - Kirschke, Elaine (2014)
The glucocorticoid receptor (GR), like many signaling proteins, depends on the Hsp90 molecular chaperone for in vivo function. Although Hsp90 is required for ligand binding in vivo, purified apoGR is capable of binding ligand with no enhancement from Hsp90. We reveal that Hsp70, known to facilitate client delivery to Hsp90, inactivates GR through partial unfolding, while Hsp90 reverses this inactivation. Full recovery of ligand binding requires ATP hydrolysis on Hsp90 and the HOP and p23 cochaperones. Surprisingly, energy from Hsp90 ATP hydrolysis appears to regulate client transfer from Hsp70, likely through a coupling of the two chaperone’s ATP cycles. Such coupling is embodied in novel contacts between Hsp90 and Hsp70 in the GR:Hsp70:Hsp90:HOP complex imaged by cryoEM. While GR released from Hsp70 is aggregation prone, release from Hsp90 protects GR from aggregation and enhances its ligand affinity. Together, this illustrates how coordinated chaperone interactions can enhance stability, function and regulation.